A sense of coherence and styles of coping with stress of students of medical and non-medical universities - Anna Jurczyszyn; Krzysztof Zdziarski (Kazimierz Wielki University, 2022)
The article relates to a sense of coherence and styles of coping with stress in a group of students of medical and non-medical universities. In the first part, a brief characteristics of the specifics of studies and future student work from both types of universities were presented. The issue of a sense of coherence and coping with stress in research was approximated closer. The study used a life orientation questionnaire (SOC-29) examining the sense of coherence and a questionnaire of coping in stressful situations (CISS). The level of a sense of coherence and strategies to deal with stress from students from medical and non-medical universities were compared. With the use of SOC-29 and CISS questionnaires, a group of 145 people were examined. Among the respondents there were 72 students from medical universities and 73 students from non-medical universities. In a group of students from medical universities, it has been shown that the level of sense of coherence is significantly different from the level of sense of coherence of non-medical students. The style focused on emotions was most often used in both student groups. There is a relationship between a style focused on emotions and a sense of coherence. In the study groups, no relationship was shown between the style concentrated on avoidance and the sense of coherence. The level of sense of coherence of students from medical universities is significantly different from the level of sense of coherence of students from non-medical universities. Students from both universities most often use the style concentrated on emotions, less often task style. The style focused on emotions correlates at a high level with a sense of coherence. The style focused on avoidance does not correlate with a sense of coherence. A relationship between an emotional style of coping with stress and a low sense of coherence is visible.